PHYSIOLOGY OF SPORT AND EXERCISE - Kenney, W. Larry; Wilmore, Jack H. 1938-2014; Costill, David L. (Human Kinetic, 2022)
Physiology of Sport and Exercise, Eighth Edition, introduces you to the fields of sport and exercise physiology. Our goal is to build on the knowledge that you developed during basic course work in human anatomy and physiology and to apply those principles in studying how the body (1) performs and responds to the added demands of an acute bout of exercise, and (2) adapts to repeated bouts of exercise, i.e., exercise training. The eighth edition of Physiology of Sport and Exercise maintains the previous edition's high standard for illustrations, photos, and medical artwork. In addition, the text is augmented with animations, audio, and video clips, provided online in the student web study guide and separately for instructors. The new edition also includes fully updated "Research Perspective" elements introduced in the last edition that highlight interesting current research. Each chapter in the book begins with a chapter outline with page numbers to help you locate material. Also noted in the chapter outline are the web study guide activities relating to each section of the chapter. Each chapter begins with a brief story that explores a real-world application of the concepts presented.